Phase II randomised discontinuation trial of brivanib in patients with advanced solid tumours. (October 2019) - Jones, Robin L.; Ratain, Mark J.; O'Dwyer, Peter J.; Siu, Lillian L.; Jassem, Jacek; Medioni, Jacques; DeJonge, Maja; Rudin, Charles; Sawyer, Michael; Khayat, David; Awada, Ahmad; de Vos-Geelen, Judith M.P.G.M.; et al.
Abstract: Background: Brivanib is a selective inhibitor of vascular endothelial growth factor and fibroblast growth factor (FGF) signalling. We performed a phase II randomised discontinuation trial of brivanib in 7 tumour types (soft-tissue sarcomas [STS], ovarian cancer, breast cancer, pancreatic cancer, non-small-cell lung cancer [NSCLC], gastric/esophageal cancer and transitional cell carcinoma [TCC]). Patients and methods: During a 12-week open-label lead-in period, patients received brivanib 800 mg daily and were evaluated for FGF2 status by immunohistochemistry. Patients with stable disease at week 12 were randomised to brivanib or placebo. A study steering committee evaluated week 12 response to determine if enrolment in a tumour type would continue. The primary objective was progression-free survival (PFS) for brivanib versus placebo in patients with FGF2-positive tumours. Results: A total of 595 patients were treated, and stable disease was observed at the week 12 randomisation point in all tumour types. Closure decisions were made for breast cancer, pancreatic cancer, NSCLC, gastric cancer and TCC. Criteria for expansion were met for STS and ovarian cancer. In 53 randomised patients with STS and FGF2-positive tumours, the median PFS was 2.8 months for brivanib and 1.4 months for placebo (hazard ratio [HR]: 0.58, p = 0.08). For all randomised patients with sarcomas, the median PFS was 2.8 months (95% confidence interval [CI]: 1.4–4.0) for those treated with brivanib compared with 1.4 months (95% CI: 1.3–1.6) for placebo (HR = 0.64, 95% CI: 0.38–1.07; p = 0.09). In the 36 randomised patients with ovarian cancer and FGF2-positive tumours, the median PFS was 4.0 (95% CI: 2.6–4.2) months for brivanib and 2.0 months (95% CI: 1.2–2.7) for placebo (HR: 0.56, 95% CI: 0.26–1.22). For all randomised patients with ovarian cancer, the median PFS in those randomised to brivanib was 4.0 months (95% CI: 2.6–4.2) and was 2.0 months (95% CI: 1.2–2.7) in those randomised to placebo (HR = 0.54, 95% CI: 0.25–1.17; p = 0.11). Conclusion: Brivanib demonstrated activity in STS and ovarian cancer with an acceptable safety profile. FGF2 expression, as defined in the protocol, is not a predictive biomarker of the efficacy of brivanib. Highlights: We performed a phase II randomised discontinuation trial of brivanib in 7 tumour types (soft-tissue sarcomas [STS], ovarian cancer, breast cancer, pancreatic cancer, non-small-cell lung cancer, gastric/esophageal cancer and transitional cell carcinoma). In 53 randomised patients with STS and fibroblast growth factor (FGF) 2–positive tumours, the median progression-free survival was 2.8 for brivanib and was 1.4 months for placebo (hazard ratio: 0.58, p = 0.08). Brivanib demonstrated activity in STS and ovarian cancer with an acceptable safety profile. FGF2 expression (per protocol) is not a predictive biomarker of the efficacy of brivanib.